2020
DOI: 10.1080/22221751.2020.1847001
|View full text |Cite
|
Sign up to set email alerts
|

A novel Sporothrix brasiliensis genomic variant in Midwestern Brazil: evidence for an older and wider sporotrichosis epidemic

Abstract: A novel Sporothrix brasiliensis genomic variant in Midwestern Brazil: evidence for an older and wider sporotrichosis epidemic Sporotrichosis is a subcutaneous infection caused by fungi from the genus Sporothrix. It is transmitted by inoculation of infective particles found in plant-contaminated material or diseased animals, characterizing the classic sapronotic and emerging zoonotic transmission, respectively. Since 1998, southeastern Brazil has experienced a zoonotic sporotrichosis epidemic caused by S. brasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…A different perspective was proposed by Eudes Filho et al. ( Eudes Filho et al. 2020 ), which suggests that the S. brasiliensis population in the city of Brasília is extremely unlikely to be derived from the one in Rio de Janeiro, as the latter has a shallow genetic diversity, suggesting an extreme bottleneck.…”
Section: Discussionmentioning
confidence: 88%
“…A different perspective was proposed by Eudes Filho et al. ( Eudes Filho et al. 2020 ), which suggests that the S. brasiliensis population in the city of Brasília is extremely unlikely to be derived from the one in Rio de Janeiro, as the latter has a shallow genetic diversity, suggesting an extreme bottleneck.…”
Section: Discussionmentioning
confidence: 88%
“…However, other studies investigating human, feline, and canine isolates of Sporothrix sp. from Brazil have identified other species, including S. schenckii sensu stricto in a canine case [ 71 ], in feline cases [ 43 , 72 ], and in humans [ 20 , 34 ], as well as S. luriei in a canine case [ 43 ], and S. globosa only in humans [ 73 ]. The description of other Sporothrix species from Brazil, including in dogs and humans from the same geographical region of this study, indicates that they may be circulating among cats in Rio de Janeiro; however, these other Sporothrix species in cats from this region have not yet been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of human sporotrichosis have been reported in almost all the 26 Brazilian states, but those directly related to cat transmission due to S. brasiliensis are highly concentered within Southwest and South regions [8], such as Sao Paulo [28], Espirito Santo [29] and Minas Gerais [30]. Recently, a case series of human zoonotic sporotrichosis has been described in Brasilia (Federal District; Midwestern Region) [31]. Only three other publications from the same region of the present study were found, two of them from Pernambuco state [18,32] and a case report of primary pulmonary sporotrichosis in an apparently immunocompetent female patient published by our group [7].…”
Section: Discussionmentioning
confidence: 99%